Penatalaksanaan Fisioterapi Pada Ischialgia Sinistra E.C Hernia Nucleus Pulposus (HNP) Di RS PKU Muhammadiyah Yogyakarta - Setianingrum, Setianingrum, Dwi Rosella Komala Sari S.Fis, M.Fis (2015)
Background : Ischialgia is a symtom of another disease which is going on such as disk herniated. Complained of pain may include pain, tingling, burning sensation, or feeling very uncomfortable throughout ischiadicus innervations or pain in the lower back and hip, then spread to the things and leg. Aims of Research : To investigate the implementation of physiotherapy in reducing pain, increasing range of motion, increasing muscle strength and functional activities in ischialgia sinistra case because hernia nucleus pulposus by using modalities of Transcutaneus Electrical Nerve Stimulation (TENS) and Neurodynamic. Result : After terapy for about six times the obtained results of the assessment of pain in static pain T0 : 2 to T6 : 1, press pain T0 : 3, to T6 : 2, motion pain T0 : 5, to T6 : 2, increasing range of motion of trunk in flexion motion T0 : 8 cm, to T6 : 10cm, extension motion T0 : 3 cm, to T6 : 4 cm, flexion movement of the right and left side no changes, increasing muscle strenght of flexor trunk T0 : 3, to T6 : 4, extensor trunk T0 = 3, to T6 = 5, flexor hip T0 = 4, to T6 = 5, extensor hip T0 = 4, to T6 = 5, flexor knee T0 = 4, to T6 = 5, dan extensor knee T0 = 4, to T6 = 5, increasing functional activities T0 : 42%, to T6 : 38%. Conclusion : Transcutaneus Electrical Nerve Stimulation (TENS) dan Neurodynamic can reduce pain, increase range of motion, increase muscle strength and functional activities in the case of ischialgia due to hernia nucleus pulposus.